ANALYSIS OF STUDENT ERRORS IN SOLVING STUDENT MATHEMATICS UAS QUESTIONS ACCORDING TO CASTOLAN CRITERIA - Mustamin Idris; Ulvina Tangke Lembang; Muh. Rizal; Rita Lefrida (JME (Journal of Mathematics Education), 2024)
This study aims to analyze the errors made by students in completing final semester exam (UAS) questions in the field of mathematics, namely linear programming, matrices and transformation geometry. The subjects of this study were students of class XI Nursing at SMK Kesehatan Indonesia Jaya Parigi. In determining the research subjects, purposive sampling technique was used . The data collection technique for this study used documentation of essay questions for the final semester exam and documentation of student answer sheets and interviews. The data analysis technique used according to Miles and Huberman is condensation of UAS and interview results data, presenting UAS and interview results data and drawing conclusions. The results of this study indicate that the errors made by students are conceptual errors, procedural errors and technical errors. Indicators of conceptual errors made by students are not being able to interpret problems/use terms, concepts, and principles, students are not able to choose formulas/properties correctly and students are not able to apply formulas/properties accurately. Indicators of procedural errors are inconsistencies in the solution steps with the questions asked and not being able to complete the questions until the final stage. Indicators of technical errors are errors in arithmetic operations and errors in moving numbers or arithmetic operations from one step to the next. Factors causing errors made by UAS participants are not understanding the questions well, lack of mastery of concepts in Matrix, Linear Programs and Transformation Geometry materials, rarely practicing reworking examples of questions, students only see and read examples of questions.